2008
DOI: 10.1053/j.gastro.2008.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-Specific Smad7 Expression Attenuates TGF-β–Mediated Fibrogenesis and Protects Against Liver Damage

Abstract: The data indicate that hepatocytes undergo TGF-beta-dependent EMT-like phenotypic changes and actively participate in fibrogenesis. Furthermore, ablation of TGF-beta signaling specifically in this cell type is sufficient to blunt the fibrogenic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
230
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(246 citation statements)
references
References 50 publications
13
230
0
2
Order By: Relevance
“…5% of the hepatic cells were coexpressing either FSP-1 and albumin or FSP-1 and β-gal, then suggestive of EMT. Moreover, in the same study the treatment with bone morphogenetic protein-7 (BMP-7), which is known to antagonize TGFβ1 signaling, significantly inhibited liver fibrosis and almost abolished putative EMT-derived fibroblasts/MFs, a result also obtained by another laboratory using transgenic mouse over-expressing Smad7 in hepatocytes [26]. The latter study also reported some morphological evidence for "in vivo" EMT in biopsies from chronic HBV patients.…”
Section: Epithelial To Mesenchymal Transition (Emt) Process and Livermentioning
confidence: 55%
“…5% of the hepatic cells were coexpressing either FSP-1 and albumin or FSP-1 and β-gal, then suggestive of EMT. Moreover, in the same study the treatment with bone morphogenetic protein-7 (BMP-7), which is known to antagonize TGFβ1 signaling, significantly inhibited liver fibrosis and almost abolished putative EMT-derived fibroblasts/MFs, a result also obtained by another laboratory using transgenic mouse over-expressing Smad7 in hepatocytes [26]. The latter study also reported some morphological evidence for "in vivo" EMT in biopsies from chronic HBV patients.…”
Section: Epithelial To Mesenchymal Transition (Emt) Process and Livermentioning
confidence: 55%
“…Given the prominent role of TGFb in EMT and fibrogenesis, a number of strategies for blocking TGF-b signaling have been proposed. [22][23][24] Small molecules targeting this signaling cascade have great therapeutic potential. To identify such candidates, a drug library screen was performed using (CAGA) 12 -Lux, a luciferase reporter that is activated in response to a wide range of TGF-b1 concentrations (Supporting Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 To date, this cell line has been used extensively as an ideal model to assess TGF-b-induced EMT on the resultant cellular phenotypes and gene expression profiles in vitro. 8,18,24 When exposed to TGF-b1 for 48 hours, AML12 cells underwent EMT, in which cells lost their epithelial honeycomb-like morphology and obtained a spindle-like shape ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β1 signaling participates in various physiological and pathological processes including embryonic development, tissue differentiation, cell proliferation, inflammation, angiogenesis, tumorigenesis as well as fibrosis (Wu et al 2016;Lei et al 2017;Li et al 2017;Tang et al 2017;Wang et al 2017;Yamazaki et al 2017;Yang et al 2017). Through regulating Smad2/3, TGF-β1 modulates the transcription and expression of several fibrosis-associated genes, thereby enhancing the synthesis of collagen and fibronectin (Dooley et al 2008;Yan and Chen 2011;Massague 2012). Overstimulation of TGF-β signaling pathway contributes to aberrant deposition of extracellular matrix (ECM), leading to the pathological heart remodeling after AMI (Dobaczewski et al 2011).…”
Section: Introductionmentioning
confidence: 99%